Linguagem e identidade: a construção discursiva das identidades sociais em interações com menores infratores - SILVA, Denilson de Souza (Universidade Federal do Pará, 2011)
This paper analyses the discourse construction of social identities in three interactions with ?juvenile offenders? in a semi-liberty juvenile detention unit. The goal of this investigation is to correlate language and identities. For this purpose, the paper first studies the ideas about the individual and his/her identification with different social centers in a modern and plural society. It also stresses the influence of institutions on the identity formation, especially the influence of institutions that deal with ?juvenile offenders? and the influence of the Children?s and adolescents? Statute. This way, the stigma, socially built, is related to the contingencies which the minors face in the verbal interactions. Hence, theory approaches that consider language in its social context such as the Interactional Sociolinguistics and the Utterance approaches are used, as well as other knowledge areas like the Cultural Studies and Social Psychology. This is an interpretative and ethnographic research that analyses the social identity construction through different footings and frames in discourse and explores the adolescents? speech in its relation with the speeches present in the unity where they are and in society. Therefore, employees and people who visit the mentioned place were interviewed, as well as observation notes about the participants? social situation were taken. The dissertation observes the most relevant emergent identities in the minors? speech such as the stigmatized identity, the religious one, the family ones and the ?identity of transformation?, always built in the necessary relation with the ?other?. The analysis reveals the conflict between the delinquent identity and the identities socially considered as ?normal?. This fact shows the complexity of social identities and makes new questions about the subject come up for future researches.